Maternal red blood cell alloimmunization requiring intrauterine transfusion: a comparative study on management and outcome depending on the type of antibody. Issue 5 (6th March 2018) - Phung, Thanh‐Vy; Houfflin‐Debarge, Véronique; Ramdane, Nassima; Ghesquière, Louise; Delsalle, Anne; Coulon, Capucine; Subtil, Damien; Vaast, Pascal; Garabedian, Charles
Abstract : BACKGROUND: The antibody primarily responsible for fetal anemia may influence treatment and prognosis. The primary objective was to compare ante‐ and postnatal management and the outcomes of maternal red blood cell (RBC) alloimmunizations according to the antibody involved. The secondary objective was to compare anti‐D alloimmunizations according to associated number of antibodies. STUDY DESIGN AND METHODS: A single‐center study from 1999 to 2015 including maternal RBC alloimmunizations requiring intrauterine transfusion (IUT) was conducted. Patients were classified according to the antibody involved: anti‐D, other Rh (anti‐c and anti‐E), and anti‐K1. Obstetric data, IUT characteristics, and neonatal outcome were compared. A specific study on the anti‐D, when isolated or associated, was then conducted. RESULTS: There were 106 pregnancies included, with 77.4% having anti‐D, 9.4% having another anti‐Rh (Rh group), and 13.2% having anti‐K1. No significant difference between the anti‐D and Rh groups was found for management and prognosis. The hemoglobin level in the first IUT was higher in the anti‐D group than in the Kell group (6.8 vs. 4.7 g/dL, p = 0.008). Newborns in the anti‐D group had significantly higher bilirubin levels and phototherapy duration than those in the Kell group. The mean estimated daily decrease in hemoglobin and that between the first two IUTs were lower with an isolated anti‐D, compared with anti‐D associated with two antibodies (p = 0.04). CONCLUSION: Anti‐K1 alloimmunizations seem to cause more severe fetal anemia than anti‐D alloimmunizations. Moreover, a decrease in hemoglobin appears to be more rapid when anti‐D is associated with other antibodies.